Kidney transplantation outcomes in patients with IgA nephropathy and other glomerular and non-glomerular primary diseases in the new era of immunosuppression. - Sophia Lionaki (Public Library of Science (PLoS), 2021)
Objectives Kidney transplant (KTx) recipients with IgAN as primary disease, were compared with recipients with other causes of renal failure, in terms of long-term outcomes. Methods Ninety-nine KTx recipients with end-stage kidney disease (ESKD) due to IgAN, were retrospectively compared to; i/ a matched case-control group of patients with non-glomerular causes of ESKD, and ii/ four control groups with ESKD due to glomerular diseases; 44 patients with primary focal segmental glomerulosclerosis (FSGS), 19 with idiopathic membranous nephropathy (IMN), 22 with lupus nephritis (LN) and 21 with pauci-immune glomerulonephritis (PIGN). Results At end of the observation period, graft function and survival, were similar between KTx recipients with IgAN and all other groups, but the rate of disease recurrence in the graft differed significantly across groups. The rate of IgAN recurrence in the graft was 23.2%, compared to 59.1% (p<0.0001) in the FSGS group, 42.1% (p = 0.17) in the IMN group, and 0% in the LN and PIGN groups (p = 0.01). IgAN recipients, who were maintained with a regimen containing tacrolimus, experienced recurrence less frequently, compared to those maintained with cyclosporine (p = 0.01). Graft loss attributed to recurrence was significantly higher in patients with FSGS versus all others. Conclusion Recipients with IgAN as primary disease, experienced outcomes comparable to those of recipients with other causes of ESKD. The rate of IgAN recurrence in the graft was significantly lower than the rate of FSGS recurrence, but higher than the one recorded in recipients with LN or PIGN. Tacrolimus, as part of the KTx maintenance therapy, was associated with lower rates of IgAN recurrence in the graft, compared to the rate cyclosporine.